Analisis Komparatif Pendekatan Behavioristik dan Konstruktivisme Sosial dalam Pembentukan Akhlak: Perspektif Neurosains Kognitif Islam: Comparative Analysis of Behavioristic Approaches and Social Constructivism in the Formation of Morals: Islamic Cognitive Neuroscience Perspective - Hisyam Syafii; Halim Purnomo (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to compare the effectiveness of behavioristic and social constructivist approaches in the formation of morals from an Islamic cognitive neuroscience perspective. The method used is library research on various related literature, including research on behavioristic theory, social constructivism, and cognitive neuroscience in Islamic education. Data were collected from academic journals and relevant Islamic studies databases. The research results show that the behavioristic approach is effective in shaping behavior through external reinforcement, while social constructivism encourages the internalization of moral values ​​through social interaction. The integration of Islamic cognitive neuroscience insights provides a more comprehensive understanding of how the brain processes and internalizes moral values. In conclusion, the combination of these two approaches, supported by a neuroscientific perspective, produces a deeper and more flexible moral formation process in the context of modern Islamic education.